Targeted Therapies for Non-Small Cell Lung Cancer - Papaetis, G. S.; Roussos, C.; Syrigos, K. N. (Current Pharmaceutical Design, 2007)
Conventional therapy for non-small cell lung cancer (NSCLC) has reached a plateau in increasing patient survival and overall prognosis still remains dismal. Advances in the knowledge of molecular events governing oncogenesis has led to a number of novel agents targeting specific pathways critical for tumour growth and survival. In the present paper we have thoroughly reviewed the existing evidence of novel agents currently studied in clinical trials, focusing on epidermal growth factor receptor family inhibitors, angiogenesis inhibitors, cyclooxygenase-2 inhibitors, Bcl-2 targeted agents, protein kinase C inhibitors, proteasome inhibitors, farnesyl transferase inhibitors and retinoids. Although erlotinib monotherapy in the second or third line setting and bevacizumab combined with conventional chemotherapy as a frontline therapy manage to prolong the life of patients with NSCLC, there is still much to be learned about the proper design of clinical trials and the selection of patient population enrolled in them. Multi-targeted therapy still remains the most attractive avenue for future treatment strategies.
Keywords: NSCLC